2001
DOI: 10.1523/jneurosci.21-12-04134.2001
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleotides Differentially Regulate Interleukin-1β Signaling in Primary Human Astrocytes: Implications for Inflammatory Gene Expression

Abstract: The cytokine interleukin-1␤ (IL-1␤) is a potent activator of human astrocytes, inducing or modulating expression of multiple proinflammatory genes via activation of the transcription factors nuclear factor-B (NF-B) and activator protein-1 (AP-1). In this study, we examined whether IL-1␤ signaling is regulated in these cells by extracellular nucleotides that are released at high concentrations under inflammatory conditions and act as ligands for members of the P2 receptor family. Using reporter constructs and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 61 publications
10
56
1
Order By: Relevance
“…The lack of effect on IL-8 production in the same culture demonstrated that 3-HAA was not simply inducing cell toxicity and apoptosis, as some studies have suggested. 48 The two ␣-chemokines (IP-10 and IL-8) are often differentially regulated, for example, by extracellular ATP or PI3K/AKT inhibitor, 49,50 in addition to 3-HAA as shown in this study. At present, the basis for the differential regulation is not clear.…”
Section: Discussionsupporting
confidence: 52%
“…The lack of effect on IL-8 production in the same culture demonstrated that 3-HAA was not simply inducing cell toxicity and apoptosis, as some studies have suggested. 48 The two ␣-chemokines (IP-10 and IL-8) are often differentially regulated, for example, by extracellular ATP or PI3K/AKT inhibitor, 49,50 in addition to 3-HAA as shown in this study. At present, the basis for the differential regulation is not clear.…”
Section: Discussionsupporting
confidence: 52%
“…Adenosine blocks TNF-mediated NF-jB activation S Majumdar and BB Aggarwal TNF-induced activation, ATP was also found to potentiate IL-1b-mediated NF-kB activation in human astrocytes (John et al, 2001). Another report showed that ATP suppresses interleukin-12 (IL-12) and TNF release from macrophages (Hasko et al, 2000a, b), which suggests that ATP may suppress NF-kB activation.…”
Section: Adenosine Blocks Tnf-mediated Nf-jb Activation S Majumdar Anmentioning
confidence: 98%
“…Indeed, suppression of lipopolysaccharide (LPS)-induced TNF production by adenosine has been demonstrated in human cardiac tissue (Wagner et al, 1998a, b). Additionally, adenosine has also been shown to modulate the signaling of inflammatory cytokines, including TNF (de la Harpe and Nathan, 1989;Sullivan et al, 1990;Bergmann et al, 1994;Liu et al, 2000) and interleukin-1 (IL-1) (Pahl 1999;John et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ATP and proinflammatory cytokines in articular tissue may well act synergistically and complementarily, because there is a true interplay between the classic inflammatory mediators and ATP in other systems. In astrocytes, P2Y modulates IL-1␤-mediated signal transduction and finetunes the transcription of genes involved in inflammatory responses in the human central nervous system (30). Conversely, IL-1␤ increases the transcription and function of P2Y 2 receptors in vascular smooth muscle cells (31) and in mammalian astrocytes (32).…”
Section: Fig 5 Effect Of Atp On Erk and P38 Mapks Phosphorylationmentioning
confidence: 99%